G alleria mellonella in vitro model for chromoblastomycosis shows large differences in virulence between isolates - Dongmei Shi; Zhiya Yang; Wanqing Liao; Chen Liu; Liang Zhao; Huilin Su; Xiaodong Wang; Huan Mei; Min Chen; Yinggai Song; Sybren de Hoog; Shuwen Deng (IMA Fungus)
Abstract Background Chromoblastomycosis is the World Health Organization (WHO)-recognized fungal implantation disease that eventually leads to severe mutilation. Cladophialophora carrionii (C. carrionii) is one of the agents. However, the pathogenesis of C. carrionii is not fully investigated yet. Methods We investigated the pathogenic potential of the fungus in a Galleria mellonella (G. mellonella) larvae infection model. Six strains of C. carrionii, and three of its environmental relative C. yegresii were tested. The G. mellonella model was also applied to determine antifungal efficacy of amphotericin B, itraconazole, voriconazole, posaconazole, and terbinafine. Results All strains were able to infect the larvae, but virulence potentials were strain-specific and showed no correlation with clinical background of the respective isolate. Survival of larvae also varied with infection dose, and with growth speed and melanization of the fungus. Posaconazole and voriconazole exhibited best activity against Cladophialophora, followed by itraconazole and terbinafine, while limited efficacy was seen for amphotericin B. Conclusion Infection behavior deviates significantly between strains. In vitro antifungal susceptibility of tested strains only partly explained the limited treatment efficacy in vivo.